Zero day : a novel - Baldacci, David (New York : Grand Central Pub., 2011)
Combat veteran John Puller, now working as an investigator for the Army's Criminal Investigative Division, tries to solve the murder of an Army man and his Pentagon contractor wife in their isolated rural home.
Keywords: United States. -- Army Criminal Investigation Command -- Officials and employees -- Fiction; Brothers -- Fiction; Murder -- Investigation -- Fiction; Conspiracy -- Fiction; Nuclear terrorism -- Fiction; West Virginia -- Fiction; Suspense fiction; Mystery fiction